Persepsi Orang Tua dan Guru dalam Penggunaan Kalimat Persuasif pada Siswa SD - Epita Meisarah; J Julia; Prana Dwija Iswara (Universitas Indraprasta PGRI Jakarta, 2022)
The background of this research is the anxiety of parents and teachers regarding the students' motivation and interest in learning which has decreased after the pandemic. This study aims to explore how the use of persuasive sentences can affect students in elementary schools. This study specifically focuses on identifying the views of parents and teachers in using persuasive sentences to increase students' interest in learning and create a conducive learning atmosphere. This study used a case study research design with the data collection using a qualitative approach by conducting interviews. The Data was collected in 2022 from 34 participants who were parents and teachers of elementary school students with 33 participants from the Bogor area and one person from the DKI Jakarta area. The results of data collection and analysis were made into several themes. The results showed that parents and teachers agreed that the use of persuasive sentences could increase interest in learning and change students' learning atmosphere. Good behavior changes are shown by students after parents and teachers use persuasive sentences. The atmosphere and interest in student learning can be changed with a sentence spoken by the teacher or the student's parents.